(untitled) (Sound Stage Screen, 2025)
In this article I discuss the reworking of the demarcation line between human and animal through the vocal sphere by referring to a dog as an "animal of interest." I draw attention to a number of recent works—paintings, performance pieces, and operas—where the figure/construct/representation of the dog and dog-human relation serves as the engine of the piece. My focus is the representation of humans that "go out of themselves," acquiring in the process animal characteristics. I am especially intrigued by how this "going out of oneself" is reflected in the voice, and whether there is something that could be called animal/dog voice and what would its characteristics be. In the first part of the article, I briefly discuss the VR opera Songs for a Passerby (2023) by director Celine Daemen, writer Olivier Herter, and music by Asa Horvitz, where a digital dog, with its full range of vocal sounds, guides the listening spectator through the piece. I continue with the example of a feral child raised by dogs and delve into artworks such as Paula Rego’s dog-women paintings and performance-art pieces by Oleg Kulik (where the artist embodies a dog). I end with the analysis of the representation of the dog/animal vocal figure in two operas by Alexander Raskatov: A Dog’s Heart (2008-9) based on Mikhail Bulgakov’s 1925 novel of the same name, and Animal Farm (2023), an adaptation of George Orwell’s 1945 timeless classic. I am especially interested in the vocal perspective of "The Posthuman as Becoming-animal" (after Rosi Braidotti). I also refer to the philosophical discussion of the so-called human-animal divide in the work of Russian philosopher Oxana Timofeeva. In her book on the posthuman, Braidotti reminds us of Deleuze’s animals classification into three groups: those we watch television with, those we eat, and those we are scared of. This ubiquity of dogs in the human world places their figure in the spotlight, particularly concerning the realm of vocal sphere. Dogs featured in the above mentioned pieces acquire voices to express their identity and perform it in a new form of relationality with human and non-human people.